Workplace Literacy Requirements and Unskilled Employment in East-Central and Western Europe - Evidence from the International Adult Literacy Survey (IALS) - János Köllő (Hungarian Academy of Sciences, Institute of Economics, 2006)
Primary degree holders have extraordinarily low employment rates in Central and East European (CEE) countries, a bias that largely contributes to their low levels of aggregate employment. The paper looks at the possible role for skills mismatch in explaining this failure. The analysis is based on data from the IALS, an international skills survey conducted in 1994-98. Multiple choice models are used to study how educational groups and jobs requiring literacy and numeracy were matched in the CEEs (Czech Republic, Hungary, Poland and Slovenia) and two groups of West-European countries. The results suggest that selection to skill-intensive jobs was more severely biased against the less-educated in the CEEs than in the rest of Europe including countries hit by high unskilled unemployment at the time of the survey (UK, Ireland, Finland). The paper concludes that the skill deficiencies of workers with primary and apprentice-based vocational qualification largely contribute to the unskilled unemployment problem in the former Communist countries, more than they do in mature European market economies.
Keywords: J01; J24; 330; Labor Economics; Human Capital; Skills; Qualifikation; Anforderungsprofil; Humankapital; Erwerbstätigkeit; Ostmitteleuropa; Westeuropa